Application of experimental design for the precipitation of calcium carbonate in the presence of biopolymer - Kirboga, Semra; Oner, Mualla (ELSEVIER, 2013)
Calcium carbonate (CaCO3) was crystallized in the presence of the water-soluble biopolymer carboxymethyl inulin (CMI ) by a precipitation method under varying experimental conditions. The CaCO3 crystals obtained were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), and BET (Brunauer, Emmett and Teller). Calcium carbonate crystals with different polymorphs and morphologies were produced by varying key parameters: the initial concentration of [Ca2+], the concentration of biopolymer and the feed rate of reactant. An experimental design procedure was applied to determine the significance of the design variables and their interaction with the specific surface area of the crystals and polymorph formation. The experimental design was studied at three levels. The range of the initial concentration of [Ca2+], the feed rate of reactant and the concentration of biopolymer were 20-100 mmol, 1-5 mL/min and 0-1 g/L, respectively. Based on these experimental conditions, model equations were proposed for the relative fraction of the vaterite polymorph and the specific surface area of the CaCO3 crystals obtained. Statistical analysis revealed that the biopolymer concentration had the greatest effect on the morphology and polymorph of calcium carbonate. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Calcium carbonate; Precipitation; Biopolymer; Vaterite; Experimental design; NEEDLE-LIKE ARAGONITE; CRYSTAL-GROWTH; SEEDED GROWTH; CARBOXYMETHYL INULIN; CACO3 NANOPARTICLES; CRYSTALLIZATION; PARTICLES; POLYELECTROLYTES; TRANSFORMATION; Engineering